Impact Force Algorithm and Parameters of Rolling Stone Impact Pier in Mountain Area - Zi-Jian Wang; Qi Liu; Yi Jiang; Li-Ming Wu; Hao Wang; Yi Wang; Ji-Wu Wang (Advances in Civil Engineering)
In mountainous bridge engineering, the impact of falling rocks on bridge piers is a critical issue. Although various algorithms have been used to calculate impact forces, there is limited research on the impact force algorithm for rolling stones hitting bridge piers. This study, based on the impulse–momentum theorem and the impact force algorithm proposed by professor Ye Siqiao, derived an impact force algorithm for rolling stones hitting bridge piers at different impact velocities and angles. Additionally, an indoor scaled-down test was designed to analyze the effects of impact velocity, angle, and position on impact force, and the results were compared with domestic and international algorithms and the calculated values of the formula derived in this paper. The results show that at an impact velocity of 3.45 m/s and an impact angle of 30°, the peak impact force reached 16.37 kN, which is a 22% increase from 12.85 kN at 2.83 m/s and a significant 53.9% increase from 10.56 kN at 2.29 m/s. Furthermore, the impact force decreased by 13.8% and 21.73% as the impact angle increased from 30° to 45° and 60°, respectively. These findings underscore the significant influence of impact velocity and angle on impact force, highlighting the necessity for accurate algorithms in engineering applications. The formula derived in this paper yielded results closest to the peak impact force, with errors between the results under each impact condition and the peak impact force fluctuating within an engineering acceptable range of ~10%, indicating that the formula derived in this paper is more accurate and reasonable for engineering applications.